The Digital Shift in the Post-COVID Era: Evaluating the Impact of Web-Enabled Education on Cognitive, Affective, and Psychomotor Skill Enhancement in Gen ‘Z’ Nursing Students- A Systematic Review with meta-analysis. - Mathivanan, Joyce Robert; Devi, Seeta (Investigación y Educación en Enfermería, 2025)
Objective. This study evaluates the impact of digital educational technologies on nursing students' academic achievement and learning outcomes. Methods. A literature review was conducted to identify peer-reviewed articles published in English between 2020 and June 2024 in databases such as Web of Science, Science Direct, EBSCO, NLM/NIH/PMC and Scopus. This review compares the efficacy of digital educational interventions against control groups using Cochrane Collaboration's risk of bias (RoB) and Standardized Mean Difference (SMD) for outcome measurement, with results analyzed using RevMan Web. Results. This study analyzed fourteen randomized controlled trials involving 1611 participants. The meta-analysis found that digital educational technologies enhanced nursing students' cognitive skills (SMD=0.45; p<0.001), critical thinking and clinical decision-making skills (SMD=0.88; p<0.001), attitudes (SMD=0.94; p<0.001), and clinical skills (SMD=1.09; p<0.001) when compared to conventional instructional methods. Nevertheless, there was no statistically significant improvement in the problem-solving ability (SMD=1.00, p=0.07). Conclusion. Recent advances in digital technology provide a spectacular opportunity to improve healthcare practices for nurses and nursing students. Their integration can potentially increase educational and professional skills, quality of life, and patient satisfaction.